PEGylation improves the therapeutic potential of dimerized translationally controlled tumor protein blocking peptide in ovalbumin-induced mouse model of airway inflammation - Hyeran Seo; Hae-Duck Bae; Haejun Pyun; Bo-Gyu Kim; Sang-Il Lee; Jin-Sook Song; Kyunglim Lee (Taylor & Francis Group, 2022)
Dimerized translationally controlled tumor protein (dTCTP) initiates a variety of allergic responses in mouse models and that dTCTP-binding peptide 2 (dTBP2) attenuates the allergic inflammation by targeting dTCTP. However, the usefulness of peptide-based drugs is often limited due to their short half-lives, rapid degradation, and high levels of clearance after systemic administration. In this study, we chemically conjugated dTBP2 with 10 kDa polyethylene glycol (PEG) to improve its therapeutic potential. N-terminal mono-PEGylated dTBP2 (PEG-dTBP2) was characterized by in vitro bioactivity assay, pharmacokinetics study, and in vivo efficacy. When compared to the unmodified dTBP2, PEG-dTBP2 reduced proinflammatory cytokine IL-8 secretion in human bronchial cells by 10 to 15% and increased plasma half-life by approximately 2.5-fold in mice. This study specifically demonstrated that PEG-dTBP2 shows higher inhibitory action against ovalbumin (OVA)-induced airway inflammation in mice compared to dTBP2. Importantly, PEG-dTBP2, when administered once at 1 mg/kg, significantly reduced the migration of inflammatory cells and the levels of cytokines in the bronchoalveolar lavage fluids as well as OVA-specific IgE levels in serum. In addition, the degree of goblet cell hyperplasia and mucus secretion were significantly attenuated in the PEG-dTBP2 group compared with the control group. These results suggest that PEG-dTBP2 can be considered a potential candidate drug for regulating allergic inflammation.